The State and Trends in the Field of Hospital Communication - Bataller-Alonso, Ernesto; Aparisi-Torrijo, Sofia; Estelles-Miguel, Sofia; Peris-Ortiz, Marta (My University, 2026)
Communication is recognized by the scientific community as one of the most important elements in thesuccess of organizations. In hospital settings, communication is also key for all those involved in patientcare, both at a strategic and operational level. This article aims to analyze the current research front onthe application and impact of communication in hospitals among healthcare professionals and/orpatients and their families, presenting the foundation, current structure and trends in academic researchin this area through bibliometric analysis using performance and impact metrics, bibliographic co-citation and keyword co-occurrence analysis. A total of 566 articles from the WoS Core Collectionpublished between 2012 and 2024 were analyzed. This is an area of growing interest but with a stilllimited impact. Collaborative networks show little synergy between international institutions, with theUSA being the country with the greatest predominance and influence. A key finding is the scientificsystematization of the origins of knowledge into four dimensions: doctor-patient communication;improving communication by reducing barriers; communication in patient transitions and discharges;and the methodologies used in this field. Current key research topics include communication betweenhealthcare professionals and patients and/or relatives, patient safety, quality improvement, and as anemerging trend, parents and communication skills. This study aims to provide researchers in the field,hospital organizations, and policymakers with an overview of research directions and a valuable source ofknowledge for defining new research lines, institutional strategies, and policies to improve patient safety
HEALTH COMMUNICATION
Keywords: Communication; hospitals; Campus Tijuana